Increased ictal perfusion of the thalamus in paroxysmal kinesigenic dyskinesia. Issue 3 (1st September 2001) - Shirane, S; Sasaki, M; Kogure, D; Matsuda, H; Hashimoto, T
Abstract : The ictal and interictal cerebral blood flow (CBF) were evaluated in a patient with right unilateral short lasting paroxysmal kinesigenic dyskinesia, by means of single photon emission computed tomography (SPECT). The patient was a 6 year old boy with no family history. During an attack, increased CBF was seen in the left thalamus. Subtraction of interictal CBF from ictal CBF disclosed a prominent increase in CBF in the left posterolateral part of the thalamus. This finding suggests that abnormal hyperactivity of thalamic neurons could be responsible for the pathophysiology of paroxysmal kinesigenic dyskinesia in this patient.